"Can you HEAR my FEAR?" A Korean immigrant with hearing loss reflects on surviving the COVID-19 pandemic in the United States - Hong, Joo Young (Disability Studies Quarterly, 2021)
This paper presents the perception and associated experiences of a Korean hard-of-hearing immigrant special education researcher as the COVID-19 pandemic unfolded. These experiences include the rise of hate crimes against Asian Americans; increasing evidence that face coverings are a vital public health tool; the knowledge that face coverings can increase the risk of racist violence; and difficulty communicating with people who are wearing most face coverings due to being hard-of-hearing. It provides supportive resources, strategies, and hope for educators, disability rights advocates, and families of individuals who are Deaf or hard-of-hearing, promoting public awareness and embrace of difference.